Reshaping agriculture to reduce obesity - Ecker, Olivier (International Food Policy Research Institute, 2019)
This chapter provides an overview of the global burden of the growing obesity epidemic and reviews regional trends in macronutrient availability. It then presents drivers of food overconsumption and explains the likely contribution of agriculture to the growing obesity epidemic in LMICs. The chapter concludes by discussing key challenges to reforming agricultural policies for reducing obesity and the potential contribution of food policy research.